The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1365-2656.2002.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer–resource interactions and cyclic population dynamics of Tanytarsus gracilentus (Diptera: Chironomidae)

Abstract: Summary 1.Tanytarsus gracilentus population dynamics in Lake Myvatn show a tendency to cycle, with three oscillations occurring between 1977 and 1999 having periods of roughly 7 years. The population abundance fluctuated over four orders of magnitude. 2. A partial autocorrelation function (PACF) accounting for measurement error revealed a strong positive lag-1 autocorrelation and a moderate negative lag-2 partial autocorrelation. This suggests that the dynamics can be explained by a simple secondorder autoregr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 57 publications
2
67
0
Order By: Relevance
“…Erratic inter-annual fluctuations in the size of the chironomid population, which are also reflected in Slavonian grebe productivity, also appear to be correlated with inter-annual changes in lake productivity indicated by DI-TP values. Our results corroborate studies in Iceland (Einarsson et al 2002;Ives et al 2008), which have suggested that chironomid population fluctuations are resource-linked and do not appear to be driven by climate or predator-prey interactions. Our study suggests that lake productivity may be the ultimate driver of chironomid population fluctuations at Loch Ruthven, which in turn affect breeding success of the Slavonian grebes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Erratic inter-annual fluctuations in the size of the chironomid population, which are also reflected in Slavonian grebe productivity, also appear to be correlated with inter-annual changes in lake productivity indicated by DI-TP values. Our results corroborate studies in Iceland (Einarsson et al 2002;Ives et al 2008), which have suggested that chironomid population fluctuations are resource-linked and do not appear to be driven by climate or predator-prey interactions. Our study suggests that lake productivity may be the ultimate driver of chironomid population fluctuations at Loch Ruthven, which in turn affect breeding success of the Slavonian grebes.…”
Section: Discussionsupporting
confidence: 91%
“…The abundance of prey species may be more significant. Studies at Myvatn, Iceland, where abundance of adult chironomids was recorded each year over 25 years and compared annually to the size of duck populations (Einarsson et al 2002Gardarsson and Einarsson 1994) suggested that the productivity of several species of duck is influenced by the abundance of non-biting midges (Diptera: Chironomidae). Small fish, particularly the threespined stickleback, Gasterosteus acutelatus, which feeds on chironomid larvae, are also an important component of the diet of adult Slavonian grebes (Fjeldså 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The adaptive and/or competitive advantages of T. gracilentus in these lakes do not, however, have to be related to oxygen regimes. Consumerresource interactions has recently been shown to be important as well (Einarsson et al 2002). The two pigmented Chi- (Table 3) and environmental variables are from Brodersen and Anderson (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced nutritive quality of the detritus is suggested by a delayed negative correlation between body size and population density of T. gracilentus observed by Einarsson et al (2002). The changes in physical structure are described by Gardarsson & Snorrason (1993) and Ólafsson and Paterson (2004).…”
Section: Speciesmentioning
confidence: 98%
“…Monitoring of the chironomid populations started in 1977 (Gardarsson et al 1995, three-spined sticklebacks (Gasterosteus aculeatus L.) in 1989 (Gíslason et al 1998), and since 1990 density of benthic Cladocera has been monitored with activity traps (Örnólfsdóttir & Einarsson 2004). Monitoring at Lake Myvatn has already yielded much insight into the long term food web dynamics of the lake, notably its oscillatory behaviour, interaction between chironomids and their sediment resources (e.g., Einarsson et al 2002) and the response of breeding duck populations to year-to-year variation in chironomid abundance (e.g., .…”
Section: Introductionmentioning
confidence: 99%